2012
DOI: 10.1155/2012/328460
|View full text |Cite
|
Sign up to set email alerts
|

The Burden of Illness in Patients with Moderate to Severe Chronic Obstructive Pulmonary Disease in Canada

Abstract: The current costs associated with moderate and severe COPD are considerable and will increase in the future. Appropriate use of medications and strategies to prevent hospitalizations for AECOPD may reduce COPD-related costs because these were the major cost drivers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 15 publications
0
29
3
1
Order By: Relevance
“…3,4,39 -42 In a Canadian study, 95% of the patients had one or more comorbidities, with cardiovascular being the most common (75.1%). 40 Mental health comorbidities are associated with and exacerbate COPD. For example, one study found only 1.5% of COPD patients suffered from substance abuse but had the largest association with increased hospital admission.…”
Section: Morbidity and Mortalitymentioning
confidence: 99%
See 4 more Smart Citations
“…3,4,39 -42 In a Canadian study, 95% of the patients had one or more comorbidities, with cardiovascular being the most common (75.1%). 40 Mental health comorbidities are associated with and exacerbate COPD. For example, one study found only 1.5% of COPD patients suffered from substance abuse but had the largest association with increased hospital admission.…”
Section: Morbidity and Mortalitymentioning
confidence: 99%
“…59 A similar study out of Canada looked at moderate to severe COPD patients and determined the mean cost per exacerbation was $3036 Canadian dollars with hospitalization representing 80% of the total. 40 There also seem to be two COPD populations: patients with frequent exacerbations and patients that do not have exacerbations. These phenotypes are highlighted in the new GOLD criteria (Fig.…”
Section: Exacerbationsmentioning
confidence: 99%
See 3 more Smart Citations